The Role of Work Motivation in Linking Organizational Support and Work Environment to Employee Performance at PT RST - Destian, Risya; Nugraha, Andhyka Tyaz; Permata, Nia Sastra; Islami, Mouna Sabira Nurul (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2025)
This study examines the influence of perceived organizational support and work environment on employee motivation and performance, as well as the mediating role of motivation. The research was conducted at PT RST, a company that needs improvements in its human resource management. Data were collected from 150 employees using a questionnaire and analyzed using the SEM-PLS method with the help of SmartPLS version 3 software. The results of the analysis indicate that organizational support has a positive effect on both motivation and employee performance. The work environment also positively influences motivation, but does not directly affect performance. Furthermore, work motivation is proven to mediate the relationship between organizational support, work environment, and employee performance. Based on these findings, it is recommended that PT RST enhance organizational support and improve the quality of the work environment to foster optimal performance and build a competitive and sustainable company.